A list of Cuban Lepidoptera (Arthropoda: Insecta) - Aguila, Rayner Núñez; Cañamero, Alejandro Barro (Zootaxa, 2012)
A total of 1557 species belonging to 56 families of the order Lepidoptera is listed from Cuba, along with the source ofeach record. Additional literature references treating Cuban Lepidoptera are also provided. The list is based primarily onliterature records, although some collections were examined: the Instituto de Ecología y Sistemática collection, Havana,Cuba; the Museo Felipe Poey collection, University of Havana; the Fernando de Zayas private collection, Havana; andthe United States National Museum collection, Smithsonian Institution, Washington DC. One family, Schreckensteinidae,and 113 species constitute new records to the Cuban fauna. The following nomenclatural changes are proposed: Paucivenahoffmanni (Koehler 1939) (Psychidae), new comb., and Gonodontodes chionosticta Hampson 1913 (Erebidae), syn. nov.,is a synonym of Gonodontodes dispar Hampson 1913. Burca cubensis (Skinner 1913) (Hesperiidae), and Eulepidotis reflexa (Herrich-Schäffer 1869) (Erebidae) are revised and revalidated.